Psychological experience of women post total abdominal hysterectomy bilateral salpingo-oophorectomy - Tukan, Ramdya Akbar (Gaceta Médica de Caracas, 2022)
Introduction: Total abdominal hysterectomy bilateral salpingo-oophorectomy (TAH BSO) is still a severe problem for women, especially in psychology. Women will feel inferior because their existence does not have several vital reproductive organs. This study explores women’s psychological experiences after TAH BSO surgery.